ÖĞRETMEN ADAYLARININ KODLAMA EĞİTİMİNE YÖNELİK GÖRÜŞLERİ: BİR DURUM ÇALIŞMASI. - GÖNCÜ, Aslı; ÇETİN, İbrahim; TOP, Ercan (Mehmet Akif Ersoy University Journal of Education Faculty, 2018)
There have been important advancements in computing education. Many countries have added computing related courses to their curriculum. This rapid change brings many questions for researchers. In this context, it is important to determine the views of teachers and pre-service teachers towards computing education. The literature seems void of studies reporting on pre-service teachers' views on computing education. In this study, it is aimed to explore information technology and software pre-service teachers' views related to computing education. For this purpose qualitative data have been obtained from 12 (3 first grade, 3 second grade, 3 third grade and 3 fourth grade) pre-service teachers through case study. In the study the data were collected by a semi-structured interview protocol. Qualitative content analysis was used in the analysis of the obtained data. Findings obtained in the research process resulted in under 9 different categories. Depending on research findings it can be said that opinions of pre-service teachers related to computing education are limited. It has been seen that pre-service teachers mentioned only about problem solving and algorithmic thinking related to computing education.